THE USE OF CHITOSAN AS A WATER CLEARANT FOR DUG WELLS IN GAMPONG JAVA BANDA ACEH - Nasution, Reni Silvia; Arfi, Febrina; Alhafiz, Alfan Ferdiansyah; Nisah, Khairun (Department of Environmental Engineering (Prodi Teknik Lingkungan), Fakultas Sains dan Teknologi, UIN Ar-Raniry Banda Aceh, 2024)
Pollution of dug well water in Gampong Jawa Banda Aceh is caused by an imbalance in the ecosystem of organic and inorganic pollutants. The purpose of this study was to determine the effect of chitosan biocoagulant as a dug-well water purifier. The stages of this research were making chitosan from shrimp shells, making chitosan biocoagulant with the addition of 1% CH3COOH, and coagulation and flocculation with various biocoagulants (0.1%, 0.2%, and 0.5%) using the jar test method with fast stirring at 150 rpm and slow stirring at 50 rpm. The results of FTIR research on chitosan were characterized by the loss of the C=O group in the deacetylation process to change the acetyl amino group in chitin to amino, with a degree of deacetylation of 93.27%. The optimum performance of biocoagulants at a concentration of 0.5% can reduce pH from 7.1 to 6.9, the turbidity level to 99.99% (NTU), and E. coli to 0 jml/mL. The conclusion from this study is that chitosan biocoagulants are able to reduce turbidity levels (NTU), pH, and Escherichia coli bacteria.